Pengaruh Budaya Organisasi, Lingkungan Kerja dan Karakteristik Individu Terhadap Kinerja Karyawan - Falya Utami Putri; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine and analyze the effect of organizational culture, work environment, and individual characteristics on employee performance in a company. This research uses quantitative methods with descriptive analysis. Data collection was carried out by distributing questionnaires to 138 employee respondents at a company. The sample used in this study was 102 respondents. The data analysis technique used in this study is the Outer Model with the calculation of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha and Inner Model with the calculation of T-statistic, f-square, and VIF using Smartpls 4.0. The results showed that all variables of Organizational Culture, Work Environment, and Individual Characteristics had a positive and significant effect on Employee Performance in a Company.